Quantitative MRCP metrics as imaging biomarkers to differentiate benign from malignant bile duct obstructions - Eurboonyanun, Kulyada; Promsorn, Julaluck; Sa-Ngiamwibool, Prakasit; Eurboonyanun, Chalerm; Finnegan, Sarah; Ferreira, Carlos; Herlihy, Amy; Shumbayawonda, Elizabeth; Lahoud, Rita Maria; Atre, Isha; O’Shea, Aileen; Harisinghani, Mukesh (Frontiers in Oncology, 2025)
BackgroundCholangiocarcinoma (CCA) is a difficult-to-detect rare cancer with high mortality rate and management costs. If detected early, surgical resection carries a 35% 5-year survival rate; this decreases to <11% 1-year survival rate when detected at later stages. Quantitative magnetic resonance cholangiopancreatography (MRCP+) provides measurements of the biliary tree and has been noted in clinical guidelines as having prognostic utility. We sought to determine whether MRCP+ metrics could differentiate benign and malignant biliary obstructions.MethodIn this retrospective study of 38 patients with biliary obstruction with histologic characterisation, 23 had malignant obstructions whilst 15 had benign obstructions. Patients underwent non-contrast and contrast MRCP alongside clinical assessment. Non-contrast MRCP images were post-processed with MRCP+. Mann-Whitney U test compared the metrics between groups. Diagnostic accuracy of MRCP+ markers (duct number and dimensions, biliary tree and gallbladder volume) to stratify benign from malignant biliary obstructions was assessed using the area under the receiver operating characteristic curve (AUC).ResultsAll bile duct metrics were significantly higher in malignant biliary obstruction (p<0.05). Of the metrics assessed, total biliary tree volume was the most clinically meaningful predictor of malignancy, with a volume of ≥25ml differentiating between the two populations. A biliary tree volume of 25ml had an AUC of 0.79 to stratify between benign and malignant obstructions.ConclusionQuantitative MRCP metrics, particularly total biliary tree volume, are shown here to differentiate malignant (CCA) from benign obstructions. As current pathways require either contrast administration or ERCP, quantitative MRCP may be an objective, non-invasive tool to identify CCA.